Till Death Do (Not) Us Part: Elderlies’ Preparation on Wealth Transmission and the Effectiveness of Testaments in Macao - Chan, Hong Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Project “HEALTHY EATING GAINS HEALTHY LIFE”: develops community to prevent non-communicable diseases (NCDs) in Macao - Cheang, Van Si (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Trust gap between government and citizens in the context of social development in Macau - Iong, Chi Long (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Exploratory study on inns and guest houses in Macao: propose monitoring system and regulatory policy - Lai, Weng Lou (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Talent management in the office of infrastructure development: a work report - Lau, Ariann Paula (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Promoting Future Elderly Social Participation In Macau: An exploratory Analysis - Leong Kai Chong; Ho, Jacky (University of Saint Joseph, 2023)
"The purpose of the research aimed to explore the challenges and future possiblities of ways of promoting elderly social participation in Macau. As lack of related research has been conduted in Macau, this community services and government policies and to provide suggestions for improving the direction of sustainable development and future possible research topics in this area. The research adopts a qualitative and phenomenological approach to explore the current situations, difficulties and ideas through the industry experience and insights. Nine in-depth interviews with 9 representatives of elderly social service providers subsidised by Macau SAR Government from late April to July 2022 in Macau. The content analysis using open coding to collect inductive data. Throughout themetic analysis identified by four levels: individials, community and social services, governmental policies and infrastructures. Overall, the study found that the autonomy trend of future social participation of the elderly in Macao is enhanced by education and self-health concerns and they are more independent, but the participation of male elders and female elders is unbalanced. Social service providers for the elderly provide a large number of repetitive services and are too passive and dependent on government policies andsupport, resulting in a lack of innovative thinking. The infrastructure design promoted by the government does not consider the continuous health and activity development of the elderly. This study looks at the ability of the elderly in Macau to continue to develop their strengths in the future, and suggests the need to strengthen individual retirement life planning and development for the elderly, personal health monitoring improvement, diversification of social services, elderly-led community programs, private social enterprise capital, and elderly volunteering The urgency of the number of elderly people, more practical and effective elderly inclusive urban planning."
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Evaluating the relationship of Filipino domestic helpers and their employers: towards improving inter-cultural community development in Macao - Lok, Weng I. (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Exploring the role of vocational education in promoting the diversification of Macao's industry: a study of the cultural and creative industries - Ngai, Hio Peng (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

The effect of managers' cultural and educational background on management style: a study of middle level managers in Macao - Tam, Hoi Iong (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Optimize the internal policym procedure and develop reform in government services: a case study on Macao immigration department for non-resident workers - Tang, Lai Ieng (University of Saint Joseph, 2013)
Keywords: Civil service; Immigration Department; Macao; Non-resident Workers; Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Workplace community development empowering employees in a public service a field research - Tong, Ka Io (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Perception About Challenges and Opportunities of Social Enterprise in Macau - Wong, Chong Chio (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph